2018
DOI: 10.1145/3264959
|View full text |Cite
|
Sign up to set email alerts
|

MindID

Abstract: Person identification technology recognizes individuals by exploiting their unique, measurable physiological and behavioral characteristics. However, the state-of-the-art person identification systems have been shown to be vulnerable, e.g., anti-surveillance prosthetic masks can thwart face recognition, contact lenses can trick iris recognition, vocoder can compromise voice identification and fingerprint films can deceive fingerprint sensors. EEG (Electroencephalography)-based identification, which utilizes th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Examples could be found in [228][229][230] where conventional factors, such as iris, retina, fingerprints, etc., are considered. Utilizing neural networks for the next-generation biometrics is the most likely way to proceed due to presently high levels of the analysis complexity [231,232].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Examples could be found in [228][229][230] where conventional factors, such as iris, retina, fingerprints, etc., are considered. Utilizing neural networks for the next-generation biometrics is the most likely way to proceed due to presently high levels of the analysis complexity [231,232].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Physionet data set used by the ref. [4][5][6], [11], [17], [20], [23], [25], [27][28], [33], and [37][38][39] and work on the publicly available dataset consisting of EEG of 109 participants completing various motor/imagery duties, it's a popular benchmark for biometric with EEG. In [9] datasets from four different experiments measuring endogenous brain functions (driving fatigue and emotion) in addition to time-locked artificially created brain responses from 157 subjects, [5] datasets including emotion and combined data.…”
Section: Datasets and Devicesmentioning
confidence: 99%
“…Additionally, the signals recorded by EEG systems must be carefully analyzed and interpreted to get useful data regarding the brain's electrical activity. In [2], [4][5][6], [9], [11], [14], [16][17][18][19], [20], [23], [25], [27][28], [30], [33], and [37][38][39] worked on BCI2000 system to record and analyzed EEG using 32 electrodes, while [1][8] [34][40] used AgCl electrodes EEG signals were recorded using a (Bio semi) Active Two system, EEG data were collected at a 512 sampling rate (Hz), AgCl with 32 electrodes works on the (10-20) of the international systems. Another device was using named GALILEO BE Light amplifier equipped with 19 channels/electrodes.…”
Section: Datasets and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that English ⟶ Romanian translations can be considered for parallel sentences of 13–28k in the case of extremely limited resources. They found that English ⟶ Romanian translation can consider 13–28k parallel sentences with extremely limited resources [ 10 ]. Akan et al proposed a speech band extension method based on Convolutional Neural Network (CNN), which is different from previous speech band extension studies and is the first.…”
Section: Related Workmentioning
confidence: 99%